2017
DOI: 10.1007/s11156-017-0623-3
|View full text |Cite
|
Sign up to set email alerts
|

Stock price reaction to profit warnings: the role of time-varying betas

Abstract: This study investigates the role of time-varying betas, event-induced variance and conditional heteroskedasticity in the estimation of abnormal returns around important news announcements. Our analysis is based on the stock price reaction to profit warnings issued by a sample of firms listed on the Hong Kong Stock Exchange. The standard event study methodology indicates the presence of price reversal patterns following both positive and negative warnings. However, incorporating time-varying betas, event-induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
1
6
0
1
Order By: Relevance
“…First, it studies a new emerging market, whereas most previous studies have focused on developed countries. Our study contributes, therefore, to closing the research gap, particularly since our results are consistent with prior literature (Yin et al, 2018;Lui et al, 2013). Second, emerging markets have provided empirical results with similar criteria to those of developed markets, which allows the researchers to compare the results in developing markets with developed markets.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…First, it studies a new emerging market, whereas most previous studies have focused on developed countries. Our study contributes, therefore, to closing the research gap, particularly since our results are consistent with prior literature (Yin et al, 2018;Lui et al, 2013). Second, emerging markets have provided empirical results with similar criteria to those of developed markets, which allows the researchers to compare the results in developing markets with developed markets.…”
Section: Introductionsupporting
confidence: 91%
“…Attracting investors is deemed to be an important issue for firms seeking to increase their capital in order to extend their investments and dominate the market. Prior studies indicate that differences in stock prices are more noticeable when timed around important news declarations (Yin et al, 2018). In addition, Lui et al (2013) found that the organized risk of individual stocks responds disproportionately to the good and bad news included within the predictor reports.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical evidences also demonstrate use of event study to gauge the reaction of the stock price behaviour with respect to positive or negative the announcement. Yin et al (2018) analysed the role of time varying betas, event induced variance and conditional heteroskedasticity in the estimation of abnormal return around important news announcements. On the basis of 1,238 positive and 485 negative profit warnings by listed companies in Hong Kong Stock Exchange, they found presence of price reversal patterns following both positive and negative warnings.…”
Section: Review and Literaturementioning
confidence: 99%
“…Return of the market in the period t The significant value of t-test at 5 per cent level of significance shows Abnormal Returns are statistically significant from zero and fraud announcement events affect the stock price of concerned banks (Adnan et al, 2016;Chakrabarti et al, 2017;Yin et al, 2018).…”
Section: Event Studymentioning
confidence: 99%
“…In particular, WTI behaved as the price setter before 2010, while Brent has played the leading role in the crude oil market since 2011 (Ji and Fan, 2015). In addition, following Yin et al (2018), we employ a paired ttest to measure whether there is a significant difference in DCC coefficients between crude oil futures markets without and with structural breaks. The results of the paired t-test shown in Table 6 provide evidence that the difference between the estimated mean values of conditional correlation coefficients is significant at the 1% level.…”
Section: Dynamic Conditional Correlations Without and With Structuralmentioning
confidence: 99%